Dark Tourism And Its Potential Impacts On Tourism Industry In Sri Lanka - Nisthar, S.; Vijayakumar, S.; Nufile, A.A.M. (South Eastern University, 2016)
This study aimed to find the likelihood of improving dark tourism and its impacts on the tourism industry in Sri Lankan context using the methodology of descriptive analysis from the secondary sources of written materials and web based documents. The main qualitative independent variables used in this study were the real and commoditized mortality of human body, the natural disastrous sites experienced and fated by the people and atrocities of genocide. There was a direct relationship between the dependant variable of dark tourism and the identified independent variables. The preservation and continuation of dark tourism potentials were instrumental in Sri Lanka. As a result, not only the present generation but the future generations as well could visit and understand how the world could never again allow a place of such hatred experiences and such persecution of existence hereafter. There were the considerable sources of improving and developing dark tourism attracting not only the inbound tourism but outbound tourism as well in Sri Lanka. Unfortunately the institutions operating within the tourism sector in Sri Lanka could not find this new trend of tourism potentiality that could be improved to increase the relative contribution of the tourism sector to Gross Domestic Product of the country. As such, the policy makers, the officials, institutions and the businesses concerned with the development of tourism sector in Sri Lanka could be made aware of the likelihood of the upliftment of tourism industry channelled through this new trend of Dark Tourism.
Keywords: Dark tourism; Mortality; Atrocities; Disaster; Gross domestic product